Flow analysis of piston head geometry for direct injection spark ignition engine - Anuar, A. R. S. (Penerbit UTM Press, 2016)
Constructors of gasoline engines face higher and higher requirements as regards to ecological issues, and increase in engine efficiency at simultaneous decrease in fuel consumption. Satisfying these requirements is possible by the recognition of the phenomena occurred inside engine cylinder, the choice of suitable optimal parameters of fuel injection process, and the determination of geometrical shapes of the combustion chamber and piston head. The aim of this study is to simulate flow in Fuel Direct-Injection engine with different geometrical shapes of piston head. Designing piston head shapes was done by referring to existing motorcycle, Demak 200cc-single cylinder using SolidWork and ANSYS software. The parameter investigated are shallow and deep bowl design of piston head. In term of fuel distribution throughout the combustion chamber, engine model that has deeper bowl (Model 2) shows better fuel distribution than model of shallow bowl as it manages to direct the fuel injected towards the location of spark plug. Total kinetic energy of Model 2 is about 20% higher than Model 1. Therefore, engine with deeper bowl is chose as the best model between the two models as it can create a richer mixture around the spark plug.